Kubernetes application developer : develop microservices and design a software solution on the cloud - Khushalani, Prateek (APRESS, 2022)
Write efficient, smart, and optimized code for containerized applications on public and private clouds at a generic level. This book shows you how to set up microservices that are robust, scalable, and capable of running on GKE (Google Kubernetes Service), AKS (Azure Kubernetes Service), ECS (Elastic Container Service), or even on a vanilla K8S cluster. The book covers the nuts and bolts of container orchestration engines (COEs) and explains how to install and configure them. It also covers creation and deployment of a sample application on COEs. You will learn how to integrate different applications such as OAuth and how to test them and secure them using Istio Citadel. You also will be taught how to create HPA rules for microservices and scale only those microservices that require it, making your stack intelligent. In the concluding chapter, the book explains how to build a SaaS solution from scratch, running on the cloud with automated deployments accessed publicly via a secured ingress K8S controller. By the end of the book, you will have a good understanding of developing microservices and how to design and create a software solution on the cloud. What You Will Learn Build software on Kubernetes in the most optimized way Interact with Kubernetes using client SDKs in Python, Go, nodejs, etc. Create a testing and deployment CI/CD system for software stacks Secure your application using Istio, without writing code Access microservices using ingress controllers and scale them using HPA rules Who This Book Is For Software and system engineers and developers.